The Semiotics of Syntax: Integrating X-Bar and Dependency Grammar in a Saussurean Framework - Doni, Chaterina Puteri; Safii, Randi; Arrashedy, Yousif Abdelmannan Mohamed Godat; Pakaya, Nurul Aini; Saleh, Sriwahyuningsih R. (Universitas Islam Negeri Raden Intan Lampung, 2025)
The Arabic language of the Qur'an exhibits a distinctive nominal sentence structure that is rich in theological and rhetorical meaning. This article presents how nominal constructions in Surah al-Maʿārij reflect theological messages and rhetorical functions through syntactic and semiotic analysis. The method used was qualitative-descriptive, with data collection techniques in the form of extracting all nominal sentences from 44 verses of the surah, then annotating and analyzing them using X-Bar Theory, Dependency Grammar, and Ferdinand de Saussure's semiotics. The research findings indicated that nominal sentences affirm the certainty of divine punishment (verses 1–2), the absence of helpers for unbelievers (verses 3–4), the transcendental authority of angels (verse 7), the ethical command to be patient with beauty (verse 8), and the semantic contrast between human perception and divine reality regarding the proximity of punishment (verses 9–10). The integration of X-Bar, Dependency Grammar, and Saussure's semiotics reveals that the syntactic variations of the Qur'an are not merely grammatical phenomena, but rather a system of signs that convey profound theological and rhetorical messages. X-Bar analysis highlights the layered projections in nominal phrases, while Dependency Grammar reveals the asymmetrical relationship between the core and its dependent that shapes the meaning of the Qur'an. From a semiotic perspective, Saussure's dyadic model of signifier and signified shows how nominal sentences function not only structurally but also symbolically in signifying divine authority and human accountability.